2021
DOI: 10.1186/s10033-021-00550-x
|View full text |Cite
|
Sign up to set email alerts
|

Friction-Induced Nanofabrication: A Review

Abstract: As the bridge between basic principles and applications of nanotechnology, nanofabrication methods play significant role in supporting the development of nanoscale science and engineering, which is changing and improving the production and lifestyle of the human. Photo lithography and other alternative technologies, such as nanoimprinting, electron beam lithography, focused ion beam cutting, and scanning probe lithography, have brought great progress of semiconductor industry, IC manufacturing and micro/nanoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Friction-induced surface amorphization of silicon materials is a common form of surface damage, which to some extent alters the performance of silicon, such as its hardness and thermal/chemical stability, leading to a significant impact on friction/wear properties. , In recent years, researchers have carried our studies on the friction-induced amorphization behavior including its influencing factors; we found that the influence mechanism of temperature, one of the most important factors during the friction process, on this amorphization process in silicon remains unclear until now. This is due to the complexity introduced by the involvement of temperature, where it is no longer the sole variable, rendering the study challenging and the underlying mechanism uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…Friction-induced surface amorphization of silicon materials is a common form of surface damage, which to some extent alters the performance of silicon, such as its hardness and thermal/chemical stability, leading to a significant impact on friction/wear properties. , In recent years, researchers have carried our studies on the friction-induced amorphization behavior including its influencing factors; we found that the influence mechanism of temperature, one of the most important factors during the friction process, on this amorphization process in silicon remains unclear until now. This is due to the complexity introduced by the involvement of temperature, where it is no longer the sole variable, rendering the study challenging and the underlying mechanism uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…An alternative way is to pattern the self-assembled film-coated surface for metal deposition [ 16 ], while the chemically bonded film on Si surface makes it difficult to penetrate the mask by scratching [ 22 ]. In addition, the pre-scratching on Si substrates can easily induce the tip wear [ 23 ]. Therefore, a mask that can resist against the solution composition and be easily penetrated by the tip scratching is crucial for the solution-based preparation of metallic micro/nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…As the manufacturing method is exceptionally important in the fabrication of microand nano-electromechanical systems (MEMS and NEMS), lithography offers various subtypes [2]. Among them, being cost-and time-effective nanoimprint lithography (NIL) is pronounced [3].…”
Section: Introductionmentioning
confidence: 99%